2004
DOI: 10.1093/humrep/deh135
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a diploid human embryonic stem cell line from a mononuclear zygote

Abstract: This method, which requires neither immuno nor mechanical removal of the trophectoderm, may facilitate the derivation of hESC lines in general, and those from abnormal embryos in particular. Furthermore, it is shown that aneuploid zygotes can be used as a source for normal hESC derivation and hold the potential to generate aneuploid hESC lines for research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 13 publications
3
39
1
1
Order By: Relevance
“…Resultant diploid embryos were previously confirmed to undergo predominantly normal fertilization owing to the asynchronous formation of two pronuclei [19,21], and a normal diploid hESC line has been derived from these oocytes [28]. These results coincide with our unpublished data, which show that, out of 16 hESC lines that are derived from one-pronuclear oocytes, the majority were of biparental origin.…”
Section: Discussionsupporting
confidence: 87%
“…Resultant diploid embryos were previously confirmed to undergo predominantly normal fertilization owing to the asynchronous formation of two pronuclei [19,21], and a normal diploid hESC line has been derived from these oocytes [28]. These results coincide with our unpublished data, which show that, out of 16 hESC lines that are derived from one-pronuclear oocytes, the majority were of biparental origin.…”
Section: Discussionsupporting
confidence: 87%
“…Human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) derived from embryos or via somatic cell reprogramming [1][2][3][4], respectively, represent a primed state of pluripotency similar to mouse epiblast stem cells (EpiSCs) [5,6] but distinct from the naïve pluripotent state of mouse ESCs and iPSCs [7]. Several studies comparing naïve and primed pluripotent stem cells have indicated that the two types of cells exhibit different molecular and functional properties, including colony morphologies, single-cell passage abilities [7,8], dependent signaling pathways [6,9,10], pluripotent gene expression profiles, and, most important, mouse embryo integration capacity to generate cross-species chimeras [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These data are very encouraging since human IVF embryos have revealed an unexpectedly high incidence of postzygotic chromosomal abnormalities which reduce the quality of recovered embryos and contribute to early pregnancy loss after embryo transfer (Delhanty & Handyside 1995, Trounson & Bongso 1996, Handyside & Delhanty 1997, Munne 2002. Surprisingly, it has been demonstrated that even aneuploid zygotes can be used as a source for derivation of hES cells (Suss-Toby et al 2004) that could be used for research purposes.…”
Section: What Is Important For the Derivation Of Hes Cells?mentioning
confidence: 93%